Critical Thinking as a Key to Solving Mathematical Problems: Findings from the TIMSS Framework in Middle Schools - Roath, Chan; Alkaki , Zhyan Rafaat Ali; James , Julie S (jurnal matematika, 2025)
Purpose of the study: The purpose of this study was to analyze the influence of critical thinking skills on students' mathematical problem solving based on the TIMSS framework. Methodology: This study uses a quantitative approach with a correlational survey design. The population of the study was junior high school students with a sample of 200 students selected by random sampling. Data collection used the Critical Thinking Ability Test and the Mathematics Problem Solving Test based on TIMSS. Data analysis was carried out using descriptive statistics, Pearson correlation tests, and simple linear regression using SPSS. Validity tests used content and construction tests, and reliability was tested with Cronbach's Alpha (0.745). Main Findings: The results of this study indicate a significant positive relationship between students' critical thinking skills and mathematical problem solving. The average score of critical thinking skills and mathematical problem solving is in the moderate category. The evaluation indicator has the highest score, while inference and synthesis have the lowest scores. The results of the Pearson correlation test showed a moderate relationship (r = 0.550), and the simple linear regression test showed that critical thinking skills significantly affect mathematical problem solving (R² = 0.303, p < 0.05). Novelty/Originality of this study: This study offers a fresh perspective by examining students’ critical thinking skills within the context of mathematical problem-solving using the TIMSS framework. The results enhance existing literature by demonstrating a strong link between critical thinking and effective problem-solving.